From macrophage polarization to clinical translation: immunomodulatory hydrogels for infection-associated bone regeneration - Zhang, Rui; Tan, Suk Fei; Wang, Ye; Wu, Junxue; Zhang, Chao (Frontiers in Cell and Developmental Biology, 2025)
Bone infections such as osteomyelitis and fracture-related infections are a significant clinical challenge, characterized by complex interactions between pathogenic microorganisms, disrupted immune responses, and impaired regenerative processes. A pathological hallmark of these conditions is the persistent pro-inflammatory macrophage (M1) polarization, which prevents the essential transition to anti-inflammatory M2 macrophages required for successful bone healing. This review examines the emerging paradigm of immunomodulatory hydrogels as a multifaceted therapeutic strategy that addresses both infection control and bone regeneration through targeted modulation of macrophage polarization. We systematically analyze the fundamental role of macrophage phenotypic switching in osteoimmune responses, demonstrating how infection disrupts the normal M1-to-M2 transition and perpetuates a chronic inflammatory state that impairs osteogenesis while promoting bone resorption. The review details innovative hydrogel design strategies that incorporate antimicrobial agents, immunomodulatory factors, and bioactive components to create materials capable of eliminating pathogens while simultaneously steering macrophages toward a pro-regenerative phenotype. Key approaches include integration of sequential drug-release systems, reactive oxygen species (ROS)-scavenging mechanisms, photothermal activation, and cell delivery platforms within biodegradable hydrogel matrices. Recent advances in multifunctional hydrogel systems have demonstrated superior performance compared to conventional treatments–including enhanced bacterial clearance, accelerated bone healing, and reduced infection recurrence rates in preclinical models. The pathway from laboratory findings to clinical application is critically evaluated, addressing challenges in biocompatibility, manufacturing consistency, regulatory approval, and clinical trial design. This comprehensive analysis reveals that immunomodulatory hydrogels represent a promising convergence of infection control and regenerative medicine, offering new therapeutic avenues for treating complex bone defects where traditional approaches have proven insufficient.